2020
DOI: 10.1136/bmjdrc-2019-000665
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of clindamycin compared with amoxicillin-metronidazole after a 7-day regimen in the treatment of periodontitis in patients with diabetes: a randomized clinical trial

Abstract: ObjectiveTo determine the efficacy of clindamycin compared with amoxicillin-metronidazole after a 7-day regimen during nonsurgical treatment of periodontitis in patients with type 2 diabetes mellitus.Research design and methodsIn this double-blind, randomized clinical trial, a total of 42 patients with chronic periodontitis and type 2 diabetes were included. Patients were randomly assigned to treatment with either clindamycin or amoxicillin-metronidazole three times a day during 7 days. Clinical determinations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…The authors noted supplementary benefits for adjunctive local antibiotic administration when compared to SRP alone in probing depth reduction and clinical attachment level gain, particularly in deep sites and well-controlled subjects [53]. These findings are in line with those of Gomez-Sandoval et al who showed that the administration of clindamycin for seven days to diabetic patients with periodontal disease has similar effects to a combination of amoxicillin and metronidazole in reducing probing depth, the bacterial plaque index and the degree of bleeding during probing [52]. Although the efficacy of amoxicillin and metronidazole has been demonstrated by multiple previous studies, clindamycin is a real and viable alternative in the treatment of periodontal infections, and should be further investigated as a potential substitute.…”
Section: The Role Of Antibiotics In Periodontal Therapy Of Diabetic Patientssupporting
confidence: 81%
See 2 more Smart Citations
“…The authors noted supplementary benefits for adjunctive local antibiotic administration when compared to SRP alone in probing depth reduction and clinical attachment level gain, particularly in deep sites and well-controlled subjects [53]. These findings are in line with those of Gomez-Sandoval et al who showed that the administration of clindamycin for seven days to diabetic patients with periodontal disease has similar effects to a combination of amoxicillin and metronidazole in reducing probing depth, the bacterial plaque index and the degree of bleeding during probing [52]. Although the efficacy of amoxicillin and metronidazole has been demonstrated by multiple previous studies, clindamycin is a real and viable alternative in the treatment of periodontal infections, and should be further investigated as a potential substitute.…”
Section: The Role Of Antibiotics In Periodontal Therapy Of Diabetic Patientssupporting
confidence: 81%
“…Some have strongly argued that the optimal periodontal therapeutic approach in diabetic patients is SRP in combination with the systemic administration of amoxicillin and metronidazole [48][49][50][51]. At the same time, Gomez-Sandoval points out that there are no studies comparing the effectiveness of the combination of amoxicillin and metronidazole with clindamycin in the periodontal therapeutic management of the diabetic patient [52]. He showed that a seven-day period of antibiotics administration was preferable in periodontal therapy, using standard doses, to the detriment of a 14-day period of administration, as this reduces side effects and minimizes costs [52].…”
Section: The Role Of Antibiotics In Periodontal Therapy Of Diabetic Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Clindamycin is a broad-spectrum bacteriostatic antibiotic that covers both aerobic and anaerobic pathogens [ 73 , 74 ]. The drug is the newer generation of lincomycin, and it has suitable potency against bone, joint, and odontogenic infections [ 73 , 74 ].…”
Section: The Most Common Prescribed Antibioticsmentioning
confidence: 99%
“…Clindamycin is a broad-spectrum bacteriostatic antibiotic that covers both aerobic and anaerobic pathogens [ 73 , 74 ]. The drug is the newer generation of lincomycin, and it has suitable potency against bone, joint, and odontogenic infections [ 73 , 74 ]. As showed by the previous investigations, nearly 75% of all bacteria causing odontogenic infections are sensitive to the drug [ 33 ].…”
Section: The Most Common Prescribed Antibioticsmentioning
confidence: 99%